Analysis of the Relationship between Corporate Branding and Sales Revenue during COVID 19 Pandemic - Molate, Mosie C. C.; Ngwakwe, Collins C.; Motubatse, Nebbel K. (International Review of Management and Marketing, 2024)
Firm internal resources have been found to influence business survival and profitability during times of crisis. This study aims to examine the relationship between corporate branding and sales revenue of multinational companies during COVID-19 pandemic. This study is based on a quantitative approach and draws on a sample of 74 global companies from various industries that the financial times ranked as prospering during the COVID-19 pandemic. The secondary data were collected from the annual financial statements of sampled companies from 2019 to 2021 and analysed using multiple regression analysis. The findings indicate that the relationship between corporate branding and sales revenue is positive, albeit statistically insignificant. These findings indicate that while corporate branding may not have a significant effect on sales revenue during economic downturn, it is vital for firms to embrace corporate branding as a resource to enhance sales revenue sustainability and thus improve profitability during crisis times such as the COVID-19 pandemic. The findings have important implication for branding managers and strategic managers in understanding the role of corporate branding in sustaining competitive advantage. Also, firms that were not prospering during COVID-19 crisis may include the investment in corporate branding in their crisis management plan and maximising firm success in the face of different environmental conditions. The results may offer an agenda for further research.